HD

( 45 x 46 + 47 x 48)x (51 x 52 -49x 48) x ( 45 x 128- 90 x 64)x (1995 x 1996 +1997 x 1998)

MV
24 tháng 4 2017 lúc 20:03

\(\left(45\cdot46+47\cdot48\right)\cdot\left(51\cdot52-49\cdot48\right)\cdot\left(45\cdot128-90\cdot64\right)\cdot\left(1995\cdot1996+1997\cdot1998\right)\)

\(=\left(45\cdot46+47\cdot48\right)\cdot\left(51\cdot52-49\cdot48\right)\cdot\left(45\cdot2\cdot64-90\cdot64\right)\cdot\left(1995\cdot1996+1997\cdot1998\right)\)

\(=\left(45\cdot46+47\cdot48\right)\cdot\left(51\cdot52-49\cdot48\right)\cdot\left(90\cdot64-90\cdot64\right)\cdot\left(1995\cdot1996+1997\cdot1998\right)\)

\(=\left(45\cdot46+47\cdot48\right)\cdot\left(51\cdot52-49\cdot48\right)\cdot0\cdot\left(1995\cdot1996+1997\cdot1998\right)\)

\(=0\)

Bình luận (0)
H24
24 tháng 4 2017 lúc 20:04

 (45 x 46 + 47 x 48) x (51 x 52 - 49 x 48) x (45 x 128 - 90 x 64) x (1995 x 1996 + 1997 x 1998)

=            A              x             B             x (45 x 128 - 45 x 2 x 64) x                C

= A x B x (45 x 128 - 45 x 128) x C

=A x B x 0 x C

=0

Bình luận (0)
NM
24 tháng 4 2017 lúc 20:04

kết quả bằng 0

Bình luận (0)
HD
24 tháng 4 2017 lúc 20:08

sorry bạn đầu tiên nha lỡ tay

Bình luận (0)
VD
24 tháng 4 2017 lúc 20:10

= 0  

vì 45 x 128 - 90 * 64 = 0

Bình luận (0)
VD
24 tháng 4 2017 lúc 20:12

tại sao -_- tui dầu tiên mà

Bình luận (0)
H24
21 tháng 6 2018 lúc 18:51

(45·46+47·48)·(51·52−49·48)·(45·128−90·64)·(1995·1996+1997·1998)

=(45·46+47·48)·(51·52−49·48)·(45·2·64−90·64)·(1995·1996+1997·1998)

=(45·46+47·48)·(51·52−49·48)·(90·64−90·64)·(1995·1996+1997·1998)

=(45·46+47·48)·(51·52−49·48)·0·(1995·1996+1997·1998)

=0

Bình luận (0)

Các câu hỏi tương tự
PB
Xem chi tiết
NM
Xem chi tiết
VH
Xem chi tiết
PB
Xem chi tiết
CB
Xem chi tiết
LN
Xem chi tiết
KT
Xem chi tiết
H24
Xem chi tiết
NM
Xem chi tiết